La « féodalité » et la seigneurie dans la Calabre méridionale normande : une institution politique pour bâtir la paix ? - Riccardo Berardi (Tabularia)
The objective of this study is to examine whether “feudalism” and lordship in southern Norman Calabria was important to reinstate peace and what were its original characters in the transition from the state of war and the new political construction of the Normans. Robert Guiscard with his brother the Great Count Roger, conquered Calabria: the centre and the north were incorporated in the duchy of Puglia and governed by Guiscard, whereas the south was united to Sicily (as definitively conquered in the last years of the 11th century) and donated to Roger I. Southern Calabria, was under the grip of the Grand Count who built the “Norman State” which would be the model of Norman Monarchy as later accomplished by his son Roger II.